Effect of graphene oxide nanosheets on the physico-mechanical properties of chitosan/bacterial cellulose nanofibrous composites. (June 2016) - Azarniya, Amir; Eslahi, Niloofar; Mahmoudi, Nafiseh; Simchi, Abdolreza
Abstract: In this work, novel chitosan/bacterial cellulose (CS/BC) nanofibrous composites reinforced with graphene oxide (GO) nanosheets are introduced. As cell attachment and permeability of nanofibrous membranes highly depend on their fiber diameter, the working window for successful electrospinning to attain sound nanofibrous composites with a minimum fiber diameter was determined by using the response surface methodology. It is shown that the addition of GO nanosheets to CS/BC significantly reduces the average size of the polymeric fibers. Their mechanical properties are also influenced and can be tailored by the concentration of GO. Fourier transform infrared spectroscopy reveals hydrogen bonding between the GO nanosheets and the polymer matrix. A decrease in the hydrophilicity of the electrospun nanofibers and their water vapor permeability with the addition of GO are also reported. The prepared nanofibrous composites are potentially suitable candidates for biomedical applications such as skin tissue engineering and wound dressing.